The Forgotten Cost of Borrowing on Public Small Business Lending Schemes: Evidence from the Fee Structure of UK Enterprise Finance Guarantee Lending - Cowling, Marc (Senate Hall, 2021)
Public loan guarantee schemes have the aim of alleviating credit constraints on small businesses by providing a gilt-edged guarantee to the lender in the event of default. In return, an interest premium is levied on loans and is paid to the government over and above that charged by the lending bank. Yet public guaranteed lending also attracts additional arrangement fees for the lender. This feature of such schemes has not been well understood despite the fact that on the current UK scheme 88.8% of issued loans and credit lines attract arrangement fees that average £2,935 per lending contract (or 2.9% of total borrowing) across the portfolio. In this paper, we explore the incidence and scale of arrangement fees and how they differ across different types of small business and lending types (credit lines versus term loans) to try and understand why fees are such an important and revealing feature of loan contracting. An important finding is that fees and interest rate are negatively correlated, implying that these two pricing elements of a loan may be compensating components of a loan's pricing structure and contract menu offered to the borrower.
Keywords: small business lending|loan guarantees|loan fees|credit rationing